2020
DOI: 10.1038/s41416-020-0747-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of H1 antihistamines in contralateral breast cancer: a Danish nationwide cohort study

Abstract: Background Preclinical studies have shown both pro- and antineoplastic effects of antihistamines. Here, we evaluated the effect of H1 antihistamines on contralateral breast cancer (CBC) risk, and whether cationic amphiphilic (CAD) antihistamines could increase the sensitivity to chemotherapy. Methods From the Danish Breast Cancer Group clinical database, we identified all women aged ≥20 years with a first-time diagnosis of breast cancer during 1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Paroxetine interacts with cytochrome P450 complex enzymes and promotes mitochondrial-induced apoptosis in astrocytes . Astemizole and other cationic amphiphilic antihistamines are currently being assessed as anticancer agents. In the context of prostate cancer, astemizole has been recently used to downregulate androgen receptor pathway via the inhibition of the polycomb repressive complex 2 (PRC2), which otherwise promotes proliferation, migration, invasion, and metastasis . Parbendazole is a benzimidazole derivative showing broad-spectrum anthelminthic activity and is also a potent microtubule poison. , Parbendazole induced apoptosis in nearly 40% of PC3 cells and inhibited cell migration by nearly 75% in wound healing assays and by 50% in invasion assays.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxetine interacts with cytochrome P450 complex enzymes and promotes mitochondrial-induced apoptosis in astrocytes . Astemizole and other cationic amphiphilic antihistamines are currently being assessed as anticancer agents. In the context of prostate cancer, astemizole has been recently used to downregulate androgen receptor pathway via the inhibition of the polycomb repressive complex 2 (PRC2), which otherwise promotes proliferation, migration, invasion, and metastasis . Parbendazole is a benzimidazole derivative showing broad-spectrum anthelminthic activity and is also a potent microtubule poison. , Parbendazole induced apoptosis in nearly 40% of PC3 cells and inhibited cell migration by nearly 75% in wound healing assays and by 50% in invasion assays.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have used preclinical evidence to investigate the role of AHs as anticancer agents. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Multiple mechanisms have been proposed for this potential effect, 9,[13][14][15]17 and they involve the use of antiproliferative, proapoptotic, and radiosensitizing properties; lysosomal cell death 9,19,20 ; and immunologic pathways. 21,22 The effectiveness of anticancer therapy can be severely limited by specific tumor types or subtypes, and new and improved anticancer drugs are always required 23 ; the repurposing of existing medication is a time-and cost-effective means of addressing this challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were administered the exogenous route of histamine dihydrochloride three times a week, resulting in a remarkable reduction in tumour size as compared to the control trial [44]. In addition, it has been shown that antagonists of the histamine H1R receptor limit cell growth and contribute to increased apoptosis through ERK activation in vitro in various tumour cell lines [45,46]. Moreover, these mechanisms only take place in the primary and HER2 breast cancer cells [47].…”
Section: Effect Of Histamine Antagonist On Breast Cancermentioning
confidence: 99%